A generic model for the study of supercontinuum generation in graphene-covered nanowires. (30th December 2021) - Linale, N; Fierens, P I; Vermeulen, N; Grosz, D F
Abstract: We study supercontinuum (SC) generation in graphene-covered nanowires based on a generic model that correctly accounts for the evolution of the photon number under Kerr and two-photon absorption processes, and the influence of graphene is treated within the framework of saturable photoexcited-carrier refraction. We discuss the role of the various effects on the generation of SC by a thorough analysis of short-pulse propagation in two different kinds of graphene-covered nanowires, one made of silicon nitride and the other made of silicon. Finally, we discuss the effect of stacking graphene layers as a means to enhance SC generation with pulse powers compatible with those in integrated optical devices.